2017
DOI: 10.1002/anie.201705209
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth–Boron Multiple Bonding in BiB2O and Bi2B

Abstract: Despite its electron deficiency, boron is versatile in forming multiple bonds. Transition-metal-boron double bonding is known, but boron-metal triple bonds have been elusive. Two bismuth boron cluster anions, BiB O and Bi B , containing triple and double B-Bi bonds are presented. The BiB O and Bi B clusters are produced by laser vaporization of a mixed B/Bi target and characterized by photoelectron spectroscopy and ab initio calculations. Well-resolved photoelectron spectra are obtained and interpreted with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…The Bi-B bond length in Bi 2 B 2 is very similar to the Bi= =B double bonds in Bi 2 B − . 9 There is a small change in the Bi-B and B-B bond lengths between the neutral and the anion. Both the Bi-B and B-B bond lengths in the linear Bi 2 B 2 cluster are slightly shorter than the Bi= =B and B= =B double bond lengths calculated from Pyykko's self-consistent atomic covalent radii of B and Bi.…”
Section: Bi 2 B 2 and Bi 2 B 2 −mentioning
confidence: 99%
See 1 more Smart Citation
“…The Bi-B bond length in Bi 2 B 2 is very similar to the Bi= =B double bonds in Bi 2 B − . 9 There is a small change in the Bi-B and B-B bond lengths between the neutral and the anion. Both the Bi-B and B-B bond lengths in the linear Bi 2 B 2 cluster are slightly shorter than the Bi= =B and B= =B double bond lengths calculated from Pyykko's self-consistent atomic covalent radii of B and Bi.…”
Section: Bi 2 B 2 and Bi 2 B 2 −mentioning
confidence: 99%
“…8 Recently, we have discovered a double-bonded Bi= =B species in Bi 2 B − ([Bi= =B= =Bi] − ) and a triple-bonded Bi≡≡B species in BiB 2 O − ([Bi≡≡B-B≡≡O] − ). 9 In the current work, we report a PES and theoretical study on a series of di-bismuth boride clusters, Bi 2 B n − (n = 2-4).…”
Section: Introductionmentioning
confidence: 99%
“…Frequency calculations were done to verify that the isomers were true minima on the potential energy surface. The inclusion of spin−orbit (SO) effects is essential for both gold and bismuth, 30,58 and previous studies on gold or gold-doped clusters have shown that inclusion of SO effects provided quantitatively better theoretical data for comparison with experimental PES spectra. 59−61 Next, single-point energies of these candidate isomers were calculated at the SODFT level using the PBE0 functional 62 and the CRENBL (ECP) 63 basis set, as implemented in the NWCHEM 6.3 package.…”
Section: Methodsmentioning
confidence: 99%
“…No unequivocal TM-bismuth triplebonded species has been reported experimentally so far, [9,14] although complexes with main-group-bismutht riple bonds (for example,B i ÀBt riple bond in BiB 2 O À )a re known. [15] Theoretical calculations suggest that the bismuthido complex [(N 3 N)W Bi]c ontains W Bi triple bond, and should be stable enough to be isolated. [12] While triple bonding between transition metals and the heavier Group 14 and Group 15 elements is known, it is confined to the Group 5and Group 6 early transition metals.…”
mentioning
confidence: 99%